Aspectos reprodutivos e alimentares da piranha Serrasalmus gouldingi fink & machado-allison, 1992 (Characiformes: Serrasalmidae) em rios afogados da Amazônia Oriental - PRUDENTE, Bruno da Silveira (Universidade Federal do Pará, 2013)
The present work aimed to evaluate the reproductive biology, condition factor and feeding ecology of Serrasalmus gouldingi in relation to fluviometric variations of lower Anapu River, in “drowned” rivers of Caxiuanã National Forest, Eastern Amazonia, Pará, Brazil. 275 specimens were bimonthly collected during July 2010 to May 2011 and their total length, total weight, gonad and stomach weight were measured. The gonads were analysed histologically to verify the sex and maturation degree, while the stomachs were evaluated through the identification of the consumed items. The sexual proportion did not differ from 1:1considering the studied period as a whole, however the females were more frequent during the transitional periods of drawdown and filing. The species spawning was “parcelada”, showing two peeks of reproductive activity during the periods which preceded the increase in the local fluviometry. The L50 was estimated in 12.24cm for males and in 16.13cm for females. The species growth was positively alometric, showing a gain of weight in relation to length, and the condition factor, when analysed along the entire sample period, decreased mostly during the spawning. The diet of S. gouldingi was composed of 32 items, grouped in 10 categories. The composition indicated an omnivorous diet with a strong tendency to piscivory, once fish fragments were the most predominant item, followed by fruits and seeds and allochthonus arthropods. The distinct hidrological periods were significantly different in relation to diet composition, although no significant difference was detected among sex and maturation degree. Males and females showed the same variation pattern of repletion index, with a more intense feeding during the increase of the river´s level, while it was less intense during the transitional periods (drawdown and filing). The species also showed some variation in their breadth niche, with lower values during the wet period, attributed to the almost exclusive consumption of fruits and seeds.